IMPLEMENTATION OF KNOWLEDGE SHARING IN MSME PRACTICES - Kurniawan, Fajar Azmi; Agus Hermawan; Naswan Suharsono (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
This article aims to analyse the implementation of Knowledge Sharing in MSME practices based on good practices carried out in one of the communities that have a focus on gathering several MSMEs to be able to synergize well. The approach used is qualitative with a case study design conducted at the Tulungagung Young Entrepreneurial Community. The results showed that: 1) Knowledge sharing was held in the form of skill upgrading workshops, licensing mechanism consultations, discussions between members related to the latest MSME issues, and training both by fellow members and from external parties such as the government; 2) The results of knowledge sharing activities have the opportunity to support the improvement of knowledge, understanding and skills of MSME actors in a fairly systematic way; 3) The obstacle faced in the implementation of knowledge sharing is that not every member can participate in programs implemented by the community so that some knowledge sharing processes have an unequal impact between members with each other. Members who regularly participate in knowledge exchange activities will obtain more information and knowledge that is useful for their entrepreneurial development practices. In the development of activities, the role of the government through policy and material support can be a strategy that needs further study.